Progress on angiogenic and antiangiogenic agents in the tumor microenvironment - Xu, Jian (Frontiers in Oncology, 2024)
The development of tumors and their metastasis relies heavily on the process of angiogenesis. When the volume of a tumor expands, the resulting internal hypoxic conditions trigger the body to enhance the production of various angiogenic factors. These include vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), platelet-derived growth factor (PDGF), and transforming growth factor-α (TGF-α), all of which work together to stimulate the activation of endothelial cells and catalyze angiogenesis. Antiangiogenic therapy (AAT) aims to normalize tumor blood vessels by inhibiting these angiogenic signals. In this review, we will explore the molecular mechanisms of angiogenesis within the tumor microenvironment, discuss traditional antiangiogenic drugs along with their limitations, examine new antiangiogenic drugs and the advantages of combination therapy, and consider future research directions in the field of antiangiogenic drugs. This comprehensive overview aims to provide insights that may aid in the development of more effective anti-tumor treatments.